Attention Control in Children With ADHD: An Investigation Using Functional Near Infrared Spectroscopy (fNIRS). Issue 8 (17th November 2022) - Calub, Catrina A.; Rapport, Mark D.; Irurita, Carolina; Eckrich, Samuel J.; Bohil, Corey
ABSTRACT: Attention problems are a predominant contributor to near- and far-term functional outcomes in attention-deficit/hyperactivity disorder (ADHD); however, most interventions focus on improving the alerting attentional network, which has failed to translate into improved learning for a majority of children with ADHD. Comparatively less is known regarding the executive attentional network and its overarching attention control process, which governs the ability to maintain relevant information in a highly active, interference-free state, and is intrinsic to a broad range of cognitive functions. This is the first study to compare attention control abilities in children with ADHD and typically developing (TD) children using the Visual Array Task (VAT) and to simultaneously measure hemodynamic functioning (oxyHb) using functional Near-Infrared Spectroscopy (fNIRS). Nineteen children with ADHD Combined type and 18 typically developing (TD) children aged 8 to 12 years were administered the VAT task while prefrontal activity was monitored using fNIRS. Results revealed that children with ADHD evinced large magnitude deficits in attention control and that oxyHb levels in the left dorsal lateral prefrontal cortex (dlPFC) were significantly greater in children with ADHD relative to TD children. These findings suggest that poor attention control abilities in children with ADHD may be related to increased left dlPFC activation in response to an underdeveloped and/or inefficient right dlPFC. The need to design interventions that target and strengthen attention control and its corresponding neural network is discussed based on the likelihood that attention control serves as the potential quaesitum for understanding a wide array of ADHD-related deficits.